Pengaruh model pembelajaran kooperatif tipe teams games tournament berbantuan aplikasi quizizz terhadap kemampuan koneksi matematis siswa - Rahayu, Deti Sri (Jurnal Pendidik Indonesia, 2024)
This study aims to analyze the effect of the cooperative learning model of the Teams Games Tournament type assisted by the Quizizz application on students' mathematical connection abilities. The research method used is a quasi-experimental design with a non-equivalent posttest-only control group design. The research sample was selected using the cluster random sampling technique, consisting of one experimental class taught using the Teams Games Tournament model assisted by Quizizz and one control class taught using conventional learning methods. After the learning process, both classes took the same posttest to measure their mathematical connection abilities. Data were collected through a mathematical connection ability test and observation sheets assessing teacher and student activities. Data analysis was conducted using the Chi-Square normality test, F-homogeneity test, and t-test for hypothesis testing. The results showed that students in the experimental class achieved an average posttest score of 71.55, while students in the control class obtained an average of 35.07. The average percentage of teacher and student activity in the experimental class was 89.28% and 86.42%, respectively, while in the control class, it was 84.37% and 85.62%. The inferential statistical analysis showed that t-calculated > t-table (2.708 > 2.433), indicating that the cooperative learning model of the Teams Games Tournament type assisted by Quizizz has a significant effect on improving students' mathematical connection abilities.